The influence of evapotranspiration on wastewater constructed wetland treatment efficiency - Albuquerque, António (2013)
Owing to low investment and maintenance costs, there has been a growing interest in applying plants in wastewater treatment. Plants commonly used in constructed wetlands (CW) include: cattail, reed, rush, yellow flag, manna grass, and willow. In a CW, application of plants brings several benefits: creating aerobic conditions in the otherwise anaerobic rhizosphere, providing carbon compounds into the rhizosphere, uptaking pollutants (e.g. nutrients and heavy metals) from treated wastewater; improving the hydraulic conditions of wastewater flow through CW beds, and also increasing the available surface for growth of microbial biofilms. Hydrophytes also have great transpiration potential. Numerous studies have shown the importance of evapotranspiration during hot periods in natural wetlands and also in constructed wetlands. Evapotranspiration affects treatment efficiency in CWs: it increases the concentration of dissolved compounds due to decreasing water volume. Therefore, having regard to the mode of operating (VSSW or HSSW), temperature and influent characteristics (e.g. HLR and wastewater influent loads), the removal efficiency calculated as a comparison between initial and final concentration is lower, than expected from mass balance. Given results from systems in colder (Poland) and warmer (Portugal) climate conditions shows that the difference in methodology of removal efficiency calculation is significant, even if the CWs are operating in different modes. Usually, in the literature removal efficiency is expressed on the basis of concentrations, mostly due to lack of flow rate monitoring. Unfortunately, this may seriously underestimate treatment performance of CWs. This study suggests the need for routine monitoring of flow rate, or evaluation of potential evapotranspiration, to estimate removal efficiency of a CW based on mass balance.